2013
DOI: 10.1080/01416200.2012.750596
|View full text |Cite
|
Sign up to set email alerts
|

Religious experience as an aim of religious education

Abstract: This article presents a model for religious education based on three central elements. First, it is argued that religious experience, or direct experience of the Divine, is an essential part of a full religious life, that religious experience is based in, enabled by and examined against, the body of knowledge in a given religion, and that religious experience is itself a form of knowing. Second, it is suggested that there be three sets of aims in religious education curriculum: knowledge aims, moral value aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The empirical facts of building tolerance character in The 2nd Senior High School Palangka Raya was a complete practice and kind of model of religious education thorough which the aim of religious education consist of knowledge, value and experience, and religious teachers became central in facilitating the pedagogical or instructional process [19]. This finding also similar to what [20] found that family relations and religion teachers were playing a pivotal role in building tolerance for students.…”
Section: Discussionsupporting
confidence: 60%
“…The empirical facts of building tolerance character in The 2nd Senior High School Palangka Raya was a complete practice and kind of model of religious education thorough which the aim of religious education consist of knowledge, value and experience, and religious teachers became central in facilitating the pedagogical or instructional process [19]. This finding also similar to what [20] found that family relations and religion teachers were playing a pivotal role in building tolerance for students.…”
Section: Discussionsupporting
confidence: 60%
“…We acknowledge that the quest to define spirituality and its role in education is a challenging topic with a wide variety of viewpoints (for example, see Court ; Dalton ). Astin et al () define spirituality as “a multifaceted quality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The most prominent thing of the last curriculum reconstruction was the scientific approach as the learning approach by activating the students (active student centered) to build the knowledge (epistemological approaches) (Yasin & Jani, 2013). Briefly, the Islamic education learning is oriented more on the activity (activitybased), not on the content or content base (Court, 2013).…”
Section: Introductionmentioning
confidence: 99%